Identification of bapA in Strains of Salmonella enterica subsp. enterica Isolated from Wild Animals Kept in Captivity in Sinaloa, Mexico - Gabriela Silva-Hidalgo; Martin López-Valenzuela; Nora Cárcamo-Aréchiga; Silvia Cota-Guajardo; Mayra López-Salazar; Edith Montiel-Vázquez (Veterinary Medicine International)
bapA, previously named stm2689, encodes the BapA protein, which, along with cellulose and fimbriae, constitutes biofilms. Biofilms are communities of microorganisms that grow in a matrix of exopolysaccharides and may adhere to living tissues or inert surfaces. Biofilm formation is associated with the ability to persist in different environments, which contributes to the pathogenicity of several species. We analyzed the presence of bapA in 83 strains belonging to 17 serovars of Salmonella enterica subsp. enterica from wildlife in captivity at Culiacan’s Zoo and Mazatlán’s Aquarium. Each isolate amplified a product of 667 bp, which corresponds to the expected size of the bapA initiator, with no observed variation between different serovars analyzed. bapA gene was found to be highly conserved in Salmonella and can be targeted for the genus-specific detection of this organism from different sources. Since bapA expression improves bacterial proliferation outside of the host and facilitates resistance to disinfectants and desiccation, the survival of Salmonella in natural habitats may be favored. Thus, the risk of bacterial contamination from these animals is increased.